Digitalization and Transformation of the Subject in the European and Ukrainian Context: A Philosophical-Anthropological Perspective - Dronov, Nikita (Вісник гуманітарних наук, 2026)
The article examines the transformation of the human subject in the context of modern digitalization through the prism of philosophical anthropology, phenomenology, digital ethics, and social philosophy. The aim is to study the transformation of the subject in the context of digitalization in the European and Ukrainian contexts from the standpoint of philosophical anthropology and modern digital ethics. Methods. The article uses an interdisciplinary approach that combines phenomenology (Bernhard Waldenfels), concepts of digital ethics (Luciano Floridi), theories of platform society (Jan van Dijk), posthumanist concepts of Rosie Braidotti, and modern studies of digital anthropology. Conclusions. The changes that occur in subjectivity under the influence of algorithmization of social practices, artificial intelligence, platform capitalism, and digital networks are analyzed. Special attention is paid to the correlation of the European and Ukrainian contexts of digitalization, in particular the impact of the 2022–2025 war on the formation of new models of digital subjectivity, digital memory and digital citizenship. It is shown that the modern subject increasingly functions as a «network subject», included in the structures of digital control, information overload and algorithmic modeling of behavior. At the same time, digital technologies create new opportunities for self-organization, cultural memory, political mobilization and expansion of communicative horizons. Results. The philosophical and anthropological potential of the new digital subject and the ethical consequences of the renewal of subjectivity are determined. It is argued that the Ukrainian experience of digitalization in war conditions demonstrates a specific form of «existential digitalization», in which digital technologies become not only a means of communication, but also a tool for survival, preservation of collective memory and cultural identity.